Olga Alexandrovna Ladyzhenskaya - Zajączkowski, Wojciech M. (Topological Methods in Nonlinear Analysis, 2005)
In January 2004 the world mathematical community lost Professor Olga Alexandrovna Ladyzhenskaya who was a great mathematician and a member of several Academies of Science. She made significant and important contributions to the area of partial differential equations, particularly the Navier-Stokes equations, nonlinear elliptic and parabolic equations